Integration of digital platforms into the structure of construction project preparation as a basis for flexible life cycle management models - MALYKHIN, Mykhailo (Ways to Improve Construction Efficiency, 2025)
Today’s digitalization of the construction sector is leading to a fundamental revision of approaches to life cycle management of built assets. The project preparation stage is acquiring particular relevance, as it lays the foundation for the effective functioning of the entire management system. Integrating digital platforms into this process ensures continuity, transparency, and flexibility of interaction among all stakeholders, creating conditions for adaptive response to change and optimized decision-making at each implementation phase. Moreover, digital solutions are forming a new management paradigm where real-time analytics, automated communication, and multi-level coordination become standard elements of the construction management digital ecosystem. This article substantiates the necessity of combining such tools as BIM modeling, ERP systems, digital twins, collaborative design platforms, monitoring dashboards, scenario modeling, and automated decision coordination mechanisms. Focusing on the preparatory phase, the authors analyze the functional capabilities of digital platforms in ensuring: (a) the integration of data on architectural, engineering, legal, and economic parameters; (b) visualization of the impact of decisions on cost, timelines, and resources; (c) coordination of actions among clients, designers, experts, municipal authorities, and contractors. The key advantages of digital environments are outlined in the context of the object’s life cycle – in particular, the formation of flexible management models that account for regulatory changes, implementation risks, and sustainable development. The paper also explores successful examples of digital platform implementation in urban infrastructure, reconstruction, industrial construction, and residential development projects. It is demonstrated that digital integration helps reduce the number of coordination cycles, enables digital verification of decisions, simplifies change management procedures, and creates the conditions for dynamic documentation updates. The authors emphasize the importance of flexible models – as those that allow a shift away from rigid linear planning in favor of adaptive scenario-based responses that consider changes in the economy, technology, and end-user demands.